The Efficiency of Belled Piles in Multi-Layers Soils Subjected to Axial Compression and Pullout Loads: Review - Abeer Ahmed Ibrahim; Mahdi Obaed Karkush (Journal of Engineering, 2023)
Multi-belled piles are piles with enlarged ends; these piles have one or further bells at the lower third part of the pile. These piles are suitable for many soils with problems such as softening clay, the variation of groundwater table, expansive soils, black cotton soil, and loose sand. The current study reviewed the behavior of belled piles in multi-layer soils subjected to axial compression and pullout loading. The review covered the experimental and theoretical works on belled piles in multi-layered soils. These piles were subjected to static and dynamic loadings in compression and pullout cases. Most theoretical results focused on software such as PLAXIS 3D. The axial load applied on the piles comes from the upper structure built above these piles, and negative skin friction comes from groundwater. The results obtained from previous studies showed the validity of using such piles in different types of soil and multilayer soils. According to previous studies, this study aims to find all the things about the belled piles, including the best shape of the belled pile being the half cone and the worst state being when the bell is fully cone. The best number of belled piles is two bells because the bearing capacity increases when the number of bells increases but does not exceed two due to hard work and high cost. The best location of a bell is at the base of the pile. The current study showed that the bearing capacity increased from 40% to 73.75% compared with ordinary piles.